Size and determinants of indirect financial distress costs : comparative analysis of syariah and non-syariah compliant firms classified as financially distressed / Nur Azri Izzati Abd Latif - Abd latif, Nur Azri Izzati (Universiti Teknologi Mara Perlis, 2020)
In this research paper, we analyze a panel data of 175 financially distressed firms to determine which firm-specific variable is reliably important in explaining the level of indirect financial distress costs. The firms are then divided into two subsections which is Non-Syariah companies and Syariah companies. Firm level yearly data from the year 2001 to 2011 was used in this research, which includes all firms listed as affected issuers under the requirement of Practice Note 4, Practice Note 17 and Amended Practice Note 17 were used. Financial distress costs were measured in terms of opportunity costs (OC). The result of the regression suggest that in the Non-Syariah companies model (Model 1) that there are two significant independent variable which is firm size and time in distress. Firm size are negatively related to the opportunity costs whereas time in distress are positively related to the opportunity costs. In the Syariah companies model (Model 2), the result of the regression suggest only one independent variable that significant to the opportunity costs which is firm size. In this model also the firm size was negatively related. Leverage, change in investment policy, intangible assets, tangible assets, expected earnings growth and liquid asset cannot be considered as proper explanatory variables of CFD.